2019
DOI: 10.1039/c9py00846b
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of mussel-inspired catechol-formaldehyde resin microspheres and their silver-based nanohybrids for catalytic and antibacterial applications

Abstract: Size-controlled CFR microspheres and their silver-based nanohybrids were constructed and the nanohybrids display high catalytic reduction activity and antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 66 publications
2
6
0
Order By: Relevance
“…These reactions can be monitored from the disappearance of the color of the dye solutions after the addition of the catalyst and excess amount of NaBH 4. [ 37,38,56 ] In line with the literature, a gradual decrease in the maximum absorbance values of 4‐NP (~410 nm) and MB (~670 nm) aqueous solutions, involving MnFe 2 O 4 @PDA‐Ag and NABH 4 , as a function of time in the UV‐Vis spectra, was observed together with the color bleaching of their aqueous solutions from yellow (4‐NP) and blue (MB) to colorless, respectively (Figure 5a,b). These results confirm the successful degradation of 4‐NP and MB to 4‐aminophenol (4‐AMP) and leucomethylene blue (LMB) forms, respectively.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These reactions can be monitored from the disappearance of the color of the dye solutions after the addition of the catalyst and excess amount of NaBH 4. [ 37,38,56 ] In line with the literature, a gradual decrease in the maximum absorbance values of 4‐NP (~410 nm) and MB (~670 nm) aqueous solutions, involving MnFe 2 O 4 @PDA‐Ag and NABH 4 , as a function of time in the UV‐Vis spectra, was observed together with the color bleaching of their aqueous solutions from yellow (4‐NP) and blue (MB) to colorless, respectively (Figure 5a,b). These results confirm the successful degradation of 4‐NP and MB to 4‐aminophenol (4‐AMP) and leucomethylene blue (LMB) forms, respectively.…”
Section: Resultssupporting
confidence: 86%
“…These results confirm the successful degradation of 4‐NP and MB to 4‐aminophenol (4‐AMP) and leucomethylene blue (LMB) forms, respectively. [ 56 ] Furthermore, it could be also concluded that the reduction of NO 2 (4‐NP) and CN (MB) chromophore groups to NN and CN was accomplished by the deposited AgNPs on MnFe 2 O 4 @PDA nanocomposite surface, respectively. [ 46,57 ]…”
Section: Resultsmentioning
confidence: 99%
“…The color bleaching of the aqueous solutions together with the leveling off the UV-Vis bands after gradual decreases were also indicated the completion of the reduction reactions successfully. These results confirmed the successful degradation of MB and RhB to their leuco forms [34,[57][58][59][60] by means of the redox reactions appearing on the surface of the electron relay systems (AgNPs) enabling the transfer of surface hydride ion electrons from BH4to the target acceptor dyes MB and RhB [48, 60,61]. Possible reduction mechanism of the MB and RhB by MnFe2O4@SiO2-Ag was illustrated in Scheme 2.…”
Section: Catalytic Properties Of Mnfe2o4@sio2-agsupporting
confidence: 61%
“…33 Recently, our research group has successfully developed a facile method to prepare size-controllable catechol-formaldehyde resin (CFR) microspheres with uniform particle size distribution by a solvothermal method under alkaline conditions. 34 The two hydroxyl groups of catechol have a similar structure to mussel functional polydopamine (PDA), so it also has many outstanding advantages of PDA. Interestingly, the catechol groups in PDA not only can be converted to quinone groups by oxidation under alkaline conditions but can also coordinate or reduce metal ions to metal nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phenolic resin organic nanomaterials have advantages of a rich surface structure, easy modification, adjustable size, low price, easy preparation, and so forth and have been widely used in the preparation of various functional materials . Recently, our research group has successfully developed a facile method to prepare size-controllable catechol-formaldehyde resin (CFR) microspheres with uniform particle size distribution by a solvothermal method under alkaline conditions . The two hydroxyl groups of catechol have a similar structure to mussel functional polydopamine (PDA), so it also has many outstanding advantages of PDA.…”
Section: Introductionmentioning
confidence: 99%